If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(n + 3) = 72 Reorder the terms: -1(3 + n) = 72 (3 * -1 + n * -1) = 72 (-3 + -1n) = 72 Solving -3 + -1n = 72 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1n = 72 + 3 Combine like terms: -3 + 3 = 0 0 + -1n = 72 + 3 -1n = 72 + 3 Combine like terms: 72 + 3 = 75 -1n = 75 Divide each side by '-1'. n = -75 Simplifying n = -75
| 9x+5x+4+9=4x+4+9x | | -3-4(3+5p)=-155 | | [7-4x]=5 | | 3/5(5m+15)=12 | | 12-3=m+4 | | 10(4x+10)=4(x+7) | | -0.25+1.75x=-1.75+2.25x | | -7+2r=-7+5r | | (7+4i)*(7+4i)= | | 7x+8=232 | | 2(24x-3.2)=4(10x+4.5) | | (2x+20)(6x-38)= | | -8(z-6)=-8z-7 | | 2k-3=15 | | 1762=598-24.25a | | 2-6b=-58 | | 11x-66x=5x | | 5.1-7p=(-9.9) | | 3b+b+40= | | -3x+2.5=1.5(x+4) | | 3453253453452345235235325+456456464564646464+x=1 | | 2x^4+3x^3-11x^2-9x+15=0 | | x+1=77 | | -1.81=.5w+3.07 | | 3000c-900=3750 | | 6(x-4)+2x=8x+12 | | -18=15-3(6c+5) | | . 7x+1=2x+6 | | 6x+5=5x-10 | | x+8=3(x+2) | | 3(y+2)-2=16 | | ((5x+3-2)*27)*5=23-4 |